Gastric cancer and paraneoplastic dermatomyositis as complications of an unrecognized juvenile polyposis syndrome - Schiemer, Moritz; Schmitt-Graeff, Annette; Brass, Volker; Hasselblatt, Peter (Zeitschrift für Gastroenterologie, 2019)
Juvenile polyposis syndrome is a rare autosomal-dominant disorder characterized by multiple hamartomatous polyps in the gastrointestinal tract. It is associated with an increased risk of gastrointestinal cancer. We report the case of a 49-year-old woman presenting with proximal muscle weakness, weight loss, severe anemia, and melena. One year before, the diagnosis of a “fundic gland polyposis” was presumed after endoscopic evaluation for iron deficiency anemia had shown numerous polyps limited to the gastric mucosa. On admission, the diagnosis of dermatomyositis was made based on laboratory results with a marked elevated creatine kinase as well as the presence of characteristic clinical findings and muscle histology. Upper endoscopy revealed multiple pedunculated, edematous polyps in the stomach without apparent cancerous lesions intraluminally. Infiltration of the muscular layer was not detectable on endoscopic ultrasound. Histopathological examination of the polyps showed smooth outer surfaces and multiple dilated cystic glands, consistent with hamartomatous juvenile-type polyps. Magnetic resonance imaging revealed a peritoneal mass close to the greater curvature of the stomach, which was identified as a poorly differentiated adenocarcinoma by laparoscopic sampling. Immunohistochemical analysis of resected polyps was remarkable for a loss of SMAD4 expression, a finding that is very commonly observed in patients with gastric juvenile polyposis syndrome. Despite initial treatment response to glucocorticoids and chemotherapy, the patient died 5 months later due to progressive illness. Patients with gastric juvenile polyposis and SMAD4 mutations are at a high risk of developing gastric cancer; hence, early gastrectomy should be considered.
Keywords: hamartomatous polyp; stomach, fundus gland polyp; iron deficiency anemia